(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article explores the development of an intelligent mechatronic module designed to synchronize the operation of robotic manipulators in machine-building production lines. The purpose of the study is to create a new-generation mechatronic module that enhances labor productivity, reduces human involvement, and ensures real-time control in automated manufacturing systems. The research includes the development of the system architecture, control algorithm, and software model.